Peningkatan Layanan Sistem Kerja dengan Program Aplikasi Manajemen Pada UPK SADU Mandiri - Saleh Yaakub; Gustinar Gustinar; Iwan Eka Putra; Etik Winarni; Ilham Pahlevi (LPPM Universitas Muhammadiyah Jambi, 2024)
The Activity Management Unit (UPK) is the unit that manages the operational activities of PNPM Mandiri Rural in the sub-district and helps BKAD coordinate meetings in the sub-district. UPK SADU Mandiri is located in Sungai Itik Village, SADU District, East Tanjung Jabung Regency, which operates in the savings and loans sector with the aim of helping the community, especially women (mothers). The problem is that most people do not have sufficient capital to open a business. Under these conditions, it is not uncommon for people to have to leave the area and even move to other areas to earn money to support their families. Due to this problem, the government is present through UPK SADU Mandiri to provide assistance in the form of business capital loans specifically for women residents of Sungai Itik Village. In the partner's work process, it turns out that they have quite serious problems, namely in terms of managing data on borrower participants and processing the loan amount. It is not uncommon for this to occur in errors, both in sloppy filing and in calculating data that is not well-structured. From this problem, a simple idea emerged to provide a solution by introducing and understanding technological developments, especially in terms of data processing for partners. The technology that will be applied is the Microsoft Office Word and Excel application programs. Partners will be directed and taught to process data using computers, namely by using word processing and number processing application programs, using internet media, with a faster, safer and more well-structured process. In terms of partner management, an operational standard will be created which will be adapted to conditions in the field so that it can truly be used as a reference and then standardized.